MODEL MEDIASI MOTIVASI PADA HUBUNGAN GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERUMAHAN RAKYAT, KAWASAN PERMUKIMAN, PERTANAHAN SURABAYA - Sugiharni, Herlin; Lindiawati; Yulianti, Emma (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This research is motivated by the importance of improving the performance of public sector employees, especially in the government bureaucracy, which is influenced by various organizational factors such as leadership style, work environment, and work motivation. The purpose of this study is to analyze the direct effect of leadership style and work environment on employee performance. Also analyze the indirect effect of leadership style and work environment on employee performance through work motivation as mediation. This research is quantitative research with sampling techniques using total sampling which means that each member of the population has the same opportunity to be selected as a sample. Respondents in this study were 200 employees of the Public Housing and Settlement Area and Land Office of Surabaya City. The study used the Structural Equation Modeling Partial Least Square (SEM-PLS) method with the help of the WarpPLS 8.0 application. The results showed that leadership style has a significant positive effect on performance, work environment has a significant positive effect on performance, work motivation has a significant positive effect on performance, leadership style has a significant positive effect on work motivation, work environment has a significant positive effect on work motivation, work motivation significantly mediates the effect of leadership style and employee performance, work motivation significantly mediates the effect of work environment and performance.